2003
DOI: 10.1063/1.1572540
|View full text |Cite
|
Sign up to set email alerts
|

A high-temperature shape-memory alloy Ni54Mn25Ga21

Abstract: A high-temperature shape-memory alloy, Ni54Mn25Ga21, was developed with a shape-memory effect of 6.1% and a martensitic transformation temperature higher than 250 °C for single crystals. The measured compressive strength and strain were 845 MPa and 20.5%, respectively, with a compressive axis along the growth direction of the rods at room temperature. One thousand thermal cycles were performed on the Ni54Mn25Ga21 without obvious changes of the martensitic structure, transformation behavior, and shape-memory ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
47
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(55 citation statements)
references
References 16 publications
8
47
0
Order By: Relevance
“…However, the SME of Ni-Mn-Ga polycrystalline alloys is still lower than that of Ni-Mn-Ga single crystal (6.1%) [7]. Ni 49.…”
Section: Shape Memory Effectmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the SME of Ni-Mn-Ga polycrystalline alloys is still lower than that of Ni-Mn-Ga single crystal (6.1%) [7]. Ni 49.…”
Section: Shape Memory Effectmentioning
confidence: 95%
“…Polycrystalline alloy has several obvious advantages comparing with the single crystal such as the improved the mechanical strength and plasticity [6]. However, related reports for TWSME polycrystalline Ni-Mn-Ga SMAs are relatively seldom and their SME of Ni-Mn-Ga polycrystalline alloys are lower than that of single crystal [6][7][8]. A strain of 0.3% was reported in polycrystalline Ni 52 Mn 24 Ga 24 with two-way thermoelastic shape memory and no obvious change of large strain was found during the phase transition process [10].…”
mentioning
confidence: 95%
“…While the Ti-Ni [6] seems attractive having 100% recovery and a quasilinear behaviour, though it possesses small elastic strain values (4%) at very high stress values above 1GPa. On the other hand, in the 20% compressive strain in the martensite phase of single crystalline Ni-Mn-Ga alloy was obtained [14]. However, the crystal faulted, thus strain in the case is not recoverable.…”
Section: Introductionmentioning
confidence: 99%
“…However, the crystal faulted, thus strain in the case is not recoverable. Authors [14] obtained 8% shape-memory effect by heating above 400 0 C.…”
Section: Introductionmentioning
confidence: 99%
“…Several papers revealed that a high martensitic transformation temperature (up to 350 • C) is observed in given Ni-Mn-Ga alloys with Ni or Mn content higher than the stoichiometric Ni 2 MnGa alloy, thus showing interesting potential as high-temperature SMAs [14,15]. Ma et al [16] reported an over 6.1% shape memory effect (SME) in Ni54-Mn25-Ga21 single crystalline alloy. Meanwhile, a well-pronounced superelastic effect as large as 6% caused by stress-induced martensitic transformation in some high-temperature single crystalline Ni-Mn-Ga alloys were reported by Chernenko et al [17].…”
Section: Introductionmentioning
confidence: 99%